A New Speed Measurement System and Its Algorithm for Medium and Low Speed Maglev Train - ZHANG Zhengfang; JIANG Jie; GAN Weiwei; LU Xueyun; ZHAO Xufeng (Kongzhi Yu Xinxi Jishu)
Aiming at the deficiencies of low-speed inaccuracy and high-speed pulse loss in the speed measurement of maglev train with counting sleepers, a speed measurement system and its algorithm based on acceleration compensation were proposed. An improved particle swarm optimization algorithm (IPSO) is used to optimize the fuzzy system parameters, and the fuzzy system is used to adaptively adjust the measurement noise parameters in the Kalman filter (KF), and the acceleration and speed measurement noise in the measured noise matrix are adaptively adjusted by constructing fuzzy rules to achieve the optimal estimation of the train speed. A test was carried out in a domestic low-speed maglev train. Effectiveness and reliability of the proposed algorithm are verified by comparing the actual speed of the vehicle with high-precision radar.